Propofol anesthesia improves stroke outcomes over isoflurane anesthesia—a longitudinal multiparametric MRI study in a rodent model of transient middle cerebral artery occlusion - Franx, Bart A. A.; van Tilborg, Geralda A. F.; van der Toorn, Annette; van Heijningen, Caroline L.; Dippel, Diederik W. J.; van der Schaaf, Irene C.; Dijkhuizen, Rick M.; , on behalf of the CONTRAST consortium (Frontiers in Neurology, 2024)
General anesthesia is routinely used in endovascular thrombectomy procedures, for which volatile gas and/or intravenous propofol are recommended. Emerging evidence suggests propofol may have superior effects on disability and/or mortality rates, but a mode-of-action underlying these class-specific effects remains unknown. Here, a moderate isoflurane or propofol dosage on experimental stroke outcomes was retrospectively compared using serial multiparametric MRI and behavioral testing. Adult male rats (N = 26) were subjected to 90-min filament-induced transient middle cerebral artery occlusion. Diffusion-, T2- and perfusion-weighted MRI was performed during occlusion, 0.5 h after recanalization, and four days into the subacute phase. Sequels of ischemic damage—blood–brain barrier integrity, cerebrovascular reactivity and sensorimotor functioning—were assessed after four days. While size and severity of ischemia was comparable between groups during occlusion, isoflurane anesthesia was associated with larger lesion sizes and worsened sensorimotor functioning at follow-up. MRI markers indicated that cytotoxic edema persisted locally in the isoflurane group early after recanalization, coinciding with burgeoning vasogenic edema. At follow-up, sequels of ischemia were further aggravated in the post-ischemic lesion, manifesting as increased blood–brain barrier leakage, cerebrovascular paralysis and cerebral hyperperfusion. These findings shed new light on how isoflurane, and possibly similar volatile agents, associate with persisting injurious processes after recanalization that contribute to suboptimal treatment outcome.